GAMBARAN DIAGNOSTIK DAN PENATALAKSANAAN PENYAKIT PARU OBSTRUKSI KRONIS RSUD. DR. PIRNGADI - MICHELLE HENDRIANI DJUANG (Universitas Prima Indonesia, 2020)
COPD is the fourth cause of death and affects> 16 million people in the United States. COPD is also a disease that raises public health attention in the world. GOLD estimates indicate that COPD will increase to be the third leading cause of death in the world by 2020. From RISKESDAS 2013 obtained through interviews with people aged â‰¥ 30 years found prevalence of COPD in Indonesia is 3.7 percent. The purpose of this study was to determine the diagnostic picture of people with COPD in dr. Pringadi . This research use descriptive-retrospective case study design, with population in the form of all medical record data of COPD patients in RSUD Dr. Pirngadi Medan treated. The data of this research are then analyzed with SPSS 20. The results of this study indicate that there are more male patients (78%) than women (22%), with the most jobs being self-employed (27 people). In anamnesis results, the main complaint of all patients with COPD is dyspnea and the most common complaint is cough accompanied by sputum production (44 people). Based on smoking history, most patients smoked for 20-40 years (68 people) with the highest number of cigarettes smoked per year from smokers who smoked> 600 cigarettes / day (58 people). While most of the management is bronkodilator in the form of combination of albuterol and ipratropium (73%), antitusif in the form of ambroksol (52%), antibiotic in the form of ceftriaxone (71%), and corticosteroid in the form of metilpredinisolon (78%), and non-medical treatment in the form of rest and diet (82%).